PENGARUH PERUBAHAN GUNA LAHAN TERHADAP PEMBEBANAN JARINGAN JALAN PERKOTAAN YOGYAKARTA - Ansusanto, J. Dwijoko; Munawar, Ahmad; Priyanto, Sigit; Wibisono, Bambang Hari (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Yogyakarta have many predicates as a city, and has special characteristics of the transportation. Travel patterns in urban areas in Yogyakarta determined by the urban characteristics population in Yogyakarta city. The spread location of work place or school that located far away from the residence tend to generate the problem to the transportation. Every day,  many movements are done for works and to schools crossing the city center that impact to the urban roads. This research goal is to analyze the factors of land use as one element of the planning that affects the efficiency of transportation. The results of the study and modeling is expected to obtain an efficient urban transportation in case Yogyakarta city. The selected case is the city of Yogyakarta, which represent the medium city. The research methods was household surveys with a questionnaire instrument for the origin-destination trip. From the origin-destination matrix, then modeling using a four-step transport model will done, to obtain the road assignment. The result is decreasing volume significantly in road network caused shorten live place in the city.